Buddy, Can You Par-a-Digm? Three Predictive Models of Deviant Development - Kruttschnitt, Candace (Journal of research in crime and delinquency, 1994)
The article examines three books related to criminology. The books considered here are "The Limits of Family Influence," by David C. Rowe, "Crime in the Making," by Robert J. Sampson and "The Creation of Dangerous Violent Criminals," by Lonnie H. Athens. Each of these three books provides a very different perspective on, and insight into, the question of how long a shadow our family environments and our heritable traits cast. According to the author Rowe uses a three-pronged critique of socialization studies in his book. Rowe carefully lays out the primary research designs for separating the effects of nature and nurture and then turns to the evidence he has gathered for his thesis. This evidence is wide ranging, studies of psychopathology, social attitudes, social class, and even parental behaviors such as warmth and control. Rowe states that the claims advanced in this book are mainly limited to working-class to professional, class contexts and similarly that the environmental extremes, child abuse and neglect-are not considered